2016
DOI: 10.1371/journal.pmed.1002081
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Adulthood Overweight, Obesity, and Cancer Risk in the Women’s Health Initiative: A Longitudinal Study from the United States

Abstract: BackgroundHigh body mass index (BMI) has become the leading risk factor of disease burden in high-income countries. While recent studies have suggested that the risk of cancer related to obesity is mediated by time, insights into the dose-response relationship and the cumulative impact of overweight and obesity during the life course on cancer risk remain scarce. To our knowledge, this study is the first to assess the impact of adulthood overweight and obesity duration on the risk of cancer in a large cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 38 publications
(38 reference statements)
8
106
0
4
Order By: Relevance
“…The increase in obesity prevalence is of great public health concern, as obesity and weight gain are independently associated with several negative health outcomes such as higher all-cause and cause-specific mortality, increased risk of cardiovascular disease, diabetes, and several types of cancer [2,3,4,5,6,7,8]. Long-term obesity (referred to as obesity duration) has also been associated with an increased risk of diabetes and obesity-related cancers [9,10]. However, factors associated with weight gain and obesity duration, and the interplay between these, are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in obesity prevalence is of great public health concern, as obesity and weight gain are independently associated with several negative health outcomes such as higher all-cause and cause-specific mortality, increased risk of cardiovascular disease, diabetes, and several types of cancer [2,3,4,5,6,7,8]. Long-term obesity (referred to as obesity duration) has also been associated with an increased risk of diabetes and obesity-related cancers [9,10]. However, factors associated with weight gain and obesity duration, and the interplay between these, are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, this study found no association between adult (age 20–74 in this study) BMI and ovarian cancer risk [16]. A recent observational study demonstrated that an increased cancer risk occurs in postmenopausal women who had both greater duration and severity of obesity [18], although it has been postulated that obesity confers greater ovarian cancer risk to premenopausal women than post-menopausal [13]. However, most studies lack sufficient numbers of pre-menopausal women to validate this theory.…”
Section: Obesity and Epithelial Ovarian Cancermentioning
confidence: 68%
“…Several studies using the expansive WHI dataset have demonstrated an increased risk of breast and pancreatic cancer in postmenopausal women with high BMI 98,99 . Additionally, the duration of time women are overweight or obese correlates with increased risk for breast and ovarian cancer 100 .…”
Section: Resultsmentioning
confidence: 99%